Інтенсивнiсть акумуляцiї кадмiю i нiкелю та рiвень їх фiтотоксичностi за сумiсної дiї на проростки кукурудзи - Гришко, В.М.; Демура, Т.А. (Видавничий дім "Академперіодика" НАН України, 2008)
Intensity of Cd and Ni accumulation at the joint action and the degree of their toxicity on maize shoots are studied. It is found that Cd and Ni are most intensively taken by the roots of shoots in the first 7 hours of stressing actions, while the metals appear in leaves only after a 7-hour-long exposition. Absorption of Cd and Ni by the roots of shoots has two-phase character. Intensity of lipid peroxidation amplifies with increase in the metals accumulation levels, and the amount of finished products of the peroxidation can be used as a primary marker of the stressing influence.